Application of the Law in the Crime of Murder With Premeditation of the Death of Women and Children in the Womb - Sukadana Sukadana; Elza Qorina Pangestika (At-Tasyrih: jurnal pendidikan dan hukum Islam, 2023)
Indonesian positive law, the form of guilt for the crime of taking the life of another person can be intentional and unintentional (negligence). Intentionality is an act that can occur with premeditation or unplanned, but what is important from an event is the existence of "intention" which is realized through the actions carried out to completion. The nature and type of this research is empirical juridical, which is a concrete explanation of the object of the problem regarding the application of the law on the crime of premeditated murder which results in leaving women and children in the womb in the Kulon Progo Police area, based on facts that occur in the field, used empirical research is research that requires objects directly in the field which are then used in the form of narratives, then empirical research is research on social reality in society. Based on the descriptions that have been explained at length in the chapters, the final conclusions are as follows The application of the law with Article 340 of the Criminal Code in the crime of premeditated murder which resulted in the death of women and children in the womb "Deliberately," meaning that the act must be intentional and the intent must arise immediately, because the intent (opzet / dolus) referred to in Article 338 is an intentional act in Article 340 is an intentional act to eliminate the lives of others formed with prior intent. The obstacles faced by investigators in the search for evidence of premeditated murder cases that resulted in the death of women and children in the womb in the Kulon Progo Police area. Keywords: Application, Murder, Premeditated